Insights into the reversibility of aluminum graphite batteries. Issue 20 (4th May 2017) - Elia, Giuseppe Antonio; Hasa, Ivana; Greco, Giorgia; Diemant, Thomas; Marquardt, Krystan; Hoeppner, Katrin; Behm, R. Jürgen; Hoell, Armin; Passerini, Stefano; Hahn, Robert
Abstract : Herein we report a novel study on the reaction mechanism of non-aqueous aluminum/graphite cell chemistry employing 1-ethyl-3-methylimidazolium chloride:aluminum trichloride (EMIMCl:AlCl3 ) as the electrolyte. Abstract : Herein we report a novel study on the reaction mechanism of non-aqueous aluminum/graphite cell chemistry employing 1-ethyl-3-methylimidazolium chloride:aluminum trichloride (EMIMCl:AlCl3 ) as the electrolyte. This work highlights new insights into the reversibility of the anion intercalation chemistry besides confirming its outstanding cycle life exceeding 2000 cycles, corresponding to more than 5 months of cycling test. The reaction mechanism, involving the intercalation of AlCl4 − in graphite, has been fully characterized by means of ex situ X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), X-ray absorption near edge structure spectroscopy (XANES) and small-angle X-ray scattering (SAXS), evidencing the accumulation of anionic species into the cathode as the main factor responsible for the slight initial irreversibility of the electrochemical process.